Parameter identification of a coupled tank liquid evel system via particle swarm optimization - Nur Azmina, Othman (2009)
This project focuses on obtaining a mathematical equation for a coupled tank liquid level system. The aim of this project is to identify and obtain the mathematical modeling utilizing Particle Swarm Optimization (PSO). The level of water in each tank is monitored by a capacitive-type probe. Signal conditioning circuits convert the measured capacitance (a function of the water level) to electrical signals in the range 0 to +5 Volt DC. Output from simulated and modeling performance are compared until n set number of iteration for error less output. The fitness function which equal to the sum of errors less square over number of iteration is later used in Visual Basic. Using Visual Basic, a GUI is developed to analyze and display both performances in terms of graph. In addition, both performances are also analyzed in terms of its transient and steady-state responses. The obtained mathematical equation can further be used for controller development such as by simulation in MATLAB/Simulink